Sistem Komunikasi Jarak Jauh Alat Pengukur Kecepatan Dan Arah Angin - Jamalludin Jamalludin (Politeknik Manufaktur Negeri Bangka Belitung, 2016)
The process of measuring wind speed and its direction is still manual and considered inefficient. The purpose of making these tools is to help get the data of speed and direction of the wind from a distance in order to work more eficient. In determining the wind speed is done by chopping round of the wind speed sensor by using an encoder while the determination of the wind direction is done by reading the orientation of magnetic hall sensor, constructed as wind direction. Utilizing the Arduino Mega 2560 Microcontroller as controller, the data is recorded with a cycle which can be set. The data that has been recorded is sent to Sim900a GSM shield in the form of SMS. Then the data is received by GSM shield the server and sent to the computer. The results of this system is able to measure and store data speed and direction of the wind from a distance. With a wind speed error of 4. 56% of the measurements manually, and wind direction indicates the actual wind direction.